RESPON TIGA KLON KUMIS KUCING (Orthosipon aristatus) TERHADAP MIKORIZA ARBUSKULA - Octivia Trisilawati (Buletin Penelitian Tanaman Rempah dan Obat, 2005)
The research aiming at the effect of arbuscular mycorrhiza to the 3 clones of  Orthosipon aristatus was conducted in the green house and laboratory of Indonesian Spices and Medicinal Crops Research Institute, Bogor in 5 months.  Completely randomized design, arranged factorially with 2 factors and 3 replications was used. First factor was the clone of  orthosipon consisted of white flower, purpel and rather purple clones, meanwhile second factor was Arbuscular Mycorrhiza (AM) inoculation (300 spores of AM/plant) consisted of: without AM,  Glomus agregatum, Mac-1 (mixed of Acaulospora sp and Glomus sp), and Mac-2 (mixed of 8 kinds of AM).  The result showed a significant effect of orthosipon  clone to the plant growth (plant height, number of leaves and stem), fresh weight of stem, dry weight of leaf and root, and leaf area index.  White flower clone showed the best growth responses to the AM inoculation (fresh weight of leaf and plant P uptake increased 41,1% to 89,59% and 48,9% to 109,2%, respectively).  Glomus agregatum inoculation resulted the highest increasing plant height, number of leaves and stem, dry weight of leaf and stem, and leaf area index of the three clones.